FAKTOR TERJADINYA TRANSFORMASI ETNOPEDAGOGI PADA SILA SESANA SISYA BRAHMANA BUDDHA DI PURI SEMARAPURA - Aditya Adnyana, Anak Agung; Winaja, I Wayan; Suasthi, I Gusti Ayu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Education that comes from local wisdom cannot only be adapted to formal education. Informal and non-formal education is a big forum in the realm of education in the family and community environment. One of them can be seen from the parampara culture of Buddhist Brahmin spiritual education which originates from the Buddhakeling paguron tradition which was passed down to one of his Sisyas in Puri Semarapura, which had an impact on the transformation into a Sisya with the Prajna Paramita character. This article aims to reveal the factors of ethnopedagogical transformation in the Sila Sesana Sisya Brahmana Buddha in Puri Semarapura. The results of the study show that there is a transformation in the realm of thoughts, words and deeds as well as gradual educational patterns through Wiku Dhang Acarya, Wiku Ngeraga and Wiku Anglokapalasraya. In this context, the role of the Sesana Sisya Brahmin Buddhist Precepts in Puri Semarapura, which are inherited in a tangible and intangible way, is important to optimize the ability of a Buddhist Brahmin to understand, act and practice the Sesana text through religious literature in actual practical life.